1997
DOI: 10.1093/ajcp/108.5.504
|View full text |Cite
|
Sign up to set email alerts
|

Is the Sanctuary WhereHelicobacter pyloriAvoids Antibacterial Treatment Intracellular?

Abstract: I s t h e S a n c t u a r y W h e r e Helicobacter pylori A v o i d s A n t i b a c t e r i a l T r e a t m e n t I n t r a c e l l u l a r ? This work was supported in part by grants 10617 and 10848 from the Swedish Medical Research Council, the Nanna Svartz Foundation (L.E.), the Department of Veterans Affairs, the support of Tom and Pat Powers Foundation, and Hilda Schwartz (D.G.).Manuscript received September 18, 1996; revision accepted February 19,1997. Address reprint requests to Dr Engstrand: Departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
46
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 9 publications
3
46
0
Order By: Relevance
“…Ultimately, infected macrophages undergo apoptosis and viable bacteria and liberated [15,16]. In view of these data, it has been suggested that Hp occupy a protected intra-cellular niche that favors bacterial persistence and contributes to treatment failure [4,8,17].…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, infected macrophages undergo apoptosis and viable bacteria and liberated [15,16]. In view of these data, it has been suggested that Hp occupy a protected intra-cellular niche that favors bacterial persistence and contributes to treatment failure [4,8,17].…”
Section: Introductionmentioning
confidence: 99%
“…[3]). In vivo, the ability of Hp to survive inside epithelial cells and macrophages contributes to organism persistence and treatment failure [4,5]. We have shown previously that type I Hp evade phagocytic killing and actively modulate their entry into macrophages, whereas the less-virulent type II strains do not [6].…”
Section: Introductionmentioning
confidence: 99%
“…But even by the most optimistic estimates, these treatments are not universally successful (26,28). This lack of efficacy appears to be due, at least in part, to the development of resistance of H. pylori strains to these antibiotics (29,30) and the persistence of organisms within gastric epithelial cells (31,32). Moreover, the widespread use of antibiotics to eradicate H. pylori infections in developing countries is both logistically and economically impractical.…”
mentioning
confidence: 99%